A Self-Reflective Study on the Importance of Learning English for Educational and Career Development: Experiences of a Business English Lecturer - Rostina Rostina (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the role of English in supporting the academic and professional development of management students, based on the lecturer’s reflections as both lecturer and researcher. As English becomes increasingly important in global education and employment, many students are required to read academic materials, complete assignments, and communicate using English. This study focuses on how English for Specific Purposes (ESP), especially Business English, helps students build discipline-related skills and prepare for real workplace communication. Using an autoethnographic approach, the researcher collected data from self-interviews, reflective teaching journals, and informal student feedback over one semester. Thematic analysis was used to identify patterns in the lecturer’s experiences and observations. The findings show that English supports students’ academic growth by helping them understand textbooks, research articles, and business case studies. Students gained confidence in reading and presenting academic information after completing guided tasks. The results also indicate that ESP based on activities such as email writing, meeting simulations, and presentations strengthened students’ employability skills. These tasks helped students feel more prepared for internships and early career responsibilities. Additionally, the study highlights the importance of reflective teaching. By analyzing classroom challenges and student needs, the lecturer was able to improve teaching strategies, select more authentic materials, and provide better support for learners. This research shows that integrating ESP with employability goals can create meaningful learning experiences for management students. When English teaching is connected to real professional contexts, students develop both language proficiency and practical communication skills. The study also encourages lecturers to use reflection as a tool to enhance teaching quality and better support students’ academic and career preparation.